State and Duration Model of Energy Consumption in A Wimax Mobile Device - Suherman, S; Mubarakah, Naemah (International Journal of Engineering and Technology, 2018)
Energy consumption in a mobile device becomes a great interest as limited battery source restricts the power to activate the device. Current battery capacity displayed on a mobile phone screen is based on current state. A more precise prediction method is important as the connected application critically depends on the power availability. This paper reports the 802.16 energy assessment and modelling. A state and duration based energy consumption prediction is proposed and compared to simulated energy measurement. The evaluation showed state trend results 0.18% deviation for training data, 0.187% for test data 1 and 0.191% for test data 2. While state and duration trends result 0.194% deviation for training data, 0.211% for test data 1 and 0.215% for test data 2.Â Â Â